2014
DOI: 10.1186/1471-2229-14-142
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome discovery of miRNAs and their targets in wheat (Triticum aestivum L.)

Abstract: BackgroundMicroRNAs (miRNAs) are small, non-coding RNAs playing essential roles in plant growth, development, and stress responses. Sequencing of small RNAs is a starting point for understanding their number, diversity, expression and possible roles in plants.ResultsIn this study, we conducted a genome-wide survey of wheat miRNAs from 11 tissues, characterizing a total of 323 novel miRNAs belonging to 276 families in wheat. A miRNA conservation analysis identified 191 wheat-specific miRNAs, 2 monocot-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 70 publications
4
100
0
Order By: Relevance
“…There also are many nonconserved, evolutionarily recent miRNAs and their corresponding targets that are present only within a few closely related species or appear to be unique to specific species (47)(48)(49). Wheat miRNA sequencing, identification, profiling, and characterization have been reported extensively (50)(51)(52)(53)(54)(55)(56). However, neither miRW1 nor its precursor has been reported, possibly because of the atypical characteristics of Iw1 and Iw2.…”
Section: Discussionmentioning
confidence: 99%
“…There also are many nonconserved, evolutionarily recent miRNAs and their corresponding targets that are present only within a few closely related species or appear to be unique to specific species (47)(48)(49). Wheat miRNA sequencing, identification, profiling, and characterization have been reported extensively (50)(51)(52)(53)(54)(55)(56). However, neither miRW1 nor its precursor has been reported, possibly because of the atypical characteristics of Iw1 and Iw2.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of target genes and the functional analysis of wheat miRNAs are also difficult, since the wheat genome has not been assembled and is poorly annotated. Recently, numerous miRNAs have been identified in wheat by deep sequencing of small RNA libraries (Yao et al 2007;Wei et al 2009;Xin et al 2010;Kantar et al 2012;Meng et al 2013;Sun et al 2014;Akdogan et al 2016), however, most of them have not been registered in the available databases. It has been observed that many wheat miRNAs are regulated by stress conditions such as drought (Akdogan et al 2016) or fungal infections (Xin et al 2010).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…It has been observed that many wheat miRNAs are regulated by stress conditions such as drought (Akdogan et al 2016) or fungal infections (Xin et al 2010). Some of them are also associated with morphology and developmental processes including plant height and flowering (Kantar et al 2012) or grain development (Meng et al 2013;Sun et al 2014).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…A number of miRNA families have now been identified in wheat, and about twenty miRNA families are conserved in diverse plant species (Yao et al, 2007;Feng et al, 2014;Han et al, 2014;Kumar et al, 2014;Sun et al, 2014). Of these, miR408 contains 21 nucleotides and has been annotated in more than 30 plant species to date, indicating a high level of conservation in different plant species (Axtell and Bowman, 2008;Kozomara and Griffiths-Jones, 2011).…”
mentioning
confidence: 99%